Numerical simulation of wave attenuation and shoreline response in a coastal region with submerged breakwater - Roh, Min; Gwon, Chang-Heon; Hwang, Sooncheol; Lee, Jooyeon; Jang, Se-Chul; Kim, Hyung-Suk (Frontiers in Marine Science, 2025)
The non-hydrostatic numerical model NHWAVE was employed to investigate the hydrodynamic behavior of a coastal region with submerged breakwater, focusing on the structural dimensions and incident wave conditions. In the numerical experiment, regular waves of varying specifications were used as incident waves, and the breakwater dimensions were adjusted based on the offshore distance from the shoreline and its vertical distance from the water surface to the crest. The above experimental conditions calculated water surface displacement and velocity at different depths. The shoreline response, including erosion and accretion, was predicted by assessing nearshore flow patterns, while the wave attenuation effect was quantified based on wave height variations. The results indicate that wave attenuation is significantly influenced by breaking-induced currents generated during wave interaction with the breakwater crest. A shorter vertical distance from submerged breakwater crest resulted in stronger breaking-induced currents. The rotational direction of vortex-induced nearshore flow patterns significantly influences shoreline response, resulting in either erosion or accretion. These findings provide insights into the hydrodynamic and sediment transport mechanisms associated with submerged breakwaters, contributing to optimizing coastal protection measures.